Envisioning 3D learning environments in environmental education: an exploration of the Konza Prairie - Webb, Natalie (Kansas State University, 2015)
“There is an alarming gap between awareness and action on [environmental issues]” (Sheppard, 2005). Public awareness of how to cope and change with these issues is lacking (Sheppard, 2004; Nicholson-Cole, 2005; Dockerty et al., 2005), but new visualization technologies can begin to bridge the gap through environmental education. Environmental education focuses on the user exploring an environment, environmental issues, problem solving and ways to mitigate these issues. While the younger generations (middle to high school students) are much more aware of current and future environmental issues than older generations, the solutions to these problems may not be so apparent. By combining the need to educate young adults about climate change, regional ecosystem climate mitigation, and ecological management for technologically driven youth, middle and high school students can better understand their environment’s impact on climate-change regulation. Through literature synthesis, documentation of existing visualization exhibits and technologies, and preliminary technology exploration, a production process, criteria, framework, and technology recommendations were established. These components informed the final storyboards, which visually organized a proposal to build a 3D learning environment focused on the Konza Prairie and its ecological management practices.
Keywords: Environmental education; 3D learning environment; Virtual reality; Ecological management; Konza Prairie; Oculus Rift; Climate Change (0404); Design (0389); Environmental education (0442)